Molecular characterization of multi-drug-resistant Staphylococcus aureus in mastitis bovine milk from a dairy farm in Anhui, China - Liu, Junjun; Wang, Xin; Bi, Chongliang; Mehmood, Khalid; Ali, Farah; Qin, Jianhua; Han, Zhaoqing (Frontiers in Veterinary Science, 2022)
Mastitis is an economically important disease in the dairy industry, which is caused by various infectious pathogens. There is limited information known about the situation of drug resistance and virulence factors of Staphylococcus aureus (S. aureus) in mastitis bovine milk in Anhui. Therefore, a total of 125 fresh milk samples from clinically mastitis-positive bovine animals were collected. The bacteria pathogens were identified via bacterial culture, Gram staining, biochemical analysis, DNA extraction, 16s rRNA amplification, and phylogenetic analysis. Drug resistance analyses were performed through drug-resistant genes and virulence genes amplification. Results showed that a total of 24.8% (31/125) bacterial isolates were isolated and identified as S. aureus by Gram straining, biochemical reactions, and 16 s rRNA genes blasting. Multiple sequence alignment analysis found that the current isolates were highly similar (96.9–100.0%) to previous isolates. Phylogenetic analysis demonstrated that S. aureus was similar with MK809241.1 isolated from food in China and wCP030426.1 isolated from a person in the United States. The bacterial isolates were detected resistant to 11 antibiotics, such as Penicillin G, SXT, Ciprofloxacin, Norfloxacin, Polymyxin B, Levofloxacin, Chloramphenicol, Clindamycin, Clarithromycin, Erythromycin, and Spectinomycin. Drug-resistant genes of blaZ, ermC, rpoB, and ant (4')-la were successfully amplified. Virulence genes of hla, nuc, clfa, and eta were found in S. aureus bacteria. The current study isolated S. aureus from milk samples and revealed its drug-resistant situation, drug-resistant genes, and virulence genes. Hence, regular monitoring of S. aureus in milk samples from dairy cows may contribute to the prevention and treatment of public health concerns causing bacteria in this region.